Fetal head circumference growth in children with specific language impairment - Whitehouse, A.; Zubrick, Stephen; Blair, E.; Newnham, J.; Hickey, M. (BMJ Publishing Group, 2012)
Objective: To characterise fetal brain growth in children with specifi c language impairment (SLI).Design: A nested case–control study. Setting- Perth, Western Australia. Participants - Thirty children meeting criteria for SLI at age 10 years were individually matched with a typically developing comparison child on sex, non-verbal ability, fetal gestational age, maternal age at conception,smoking and alcohol intake during pregnancy. Main outcome measures Occipitofrontalhead circumference (HC) was measured using ultrasonography at approximately 18 weeks gestation.Femur length provided a measure of fetal length. Occipitofrontal HC was measured at birth and at the 1-year postnatal follow-up using a precise paper tape measure, while crown-heel length acted as an index of body length at both time points. Raw data were transformed to z-scores using reference norms.